CACING PARASIT PADA Nycticebus coucang - L.E. Setyorini; Wirdateti (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2005)
Seventeen slow loris, Nycticebus coucang were examined for the endoparasitic occurrence, four are alive and the others are cadavers. Eggs, embryonated eggs and larvae of Enterobius sp. (Nematode: Oxyuridae ) were found on the fecal examination. The adult and mature helminth of Syphacia sp. (Nematode: Oxyuridae) and Rictularia sp. (Nematode: Rictularidae), a species of the tape worm and species of the hook worm were found on the necropsy of thirteen cadavers.